Insidensi Serangan Hama Hypothenemus hampei Ferr Pada Budidaya Kopi Berpohon Pelindung dan Tanpa Pohon Pelindung Serta Upaya Pengendaliannya Menggunakan Perangkap Atraktan - Warlinson Girsang; Rosmadelina Purba; Rio Pradana Muliyandra (Faculty of Agriculture University of Singaperbangsa Karawang, 2021)
In Simalungun Regency of North Sumatra, pest attacks of coffee fruit grinder Hypothenemus hampei Ferr are scattered throughout the coffee producing sub-district, with the intensity of moderate – heavy attacks. The widespread spread and high intensity of attacks, because generally farmers do not make control efforts by various limitations. Including technical culture practices, farmers do not all implement agronomical strategy that can prevent pest attacks. Field experimental was conducted on 2 types of coffee plantations with different of agronomical acts, using randomized design methods of series groups. Factors studied were the influence of protective trees and experiments tested 3 types of attracktant traps to control the attack of H. hampei Ferr. The research aimed to determine the incidence level of H. hampei Ferr pest attacks on protective tree-lined and treeless coffee plants and to determine the effectiveness of attracktan traps controlling coffee fruit grinding pests. To obtain the data, the experiment was made on both types of land. The calculated parameter were : (1). Intensity of attack of coffee fruit grinding pests before the installation of attracktant. (2). Number of coffee fruit grinders trapped attracktant, (3). Other types of insects trapped besides H.hampei Ferr, and (4). The intensity of coffee fruit grinding attacks after attracktant installation, was calculated using the formula: Is = A/(A+B) x 100% (Is = attack intensity, A = number of stricken seeds, and B = healthy number of seeds). Inferred, the intensity of attacks by coffee fruit-growing pests on coffee plantations with protective trees was lower than that of coffee plantations without protective trees. The use of attracktant traps on coffee plants with protective trees and without protective trees, is able to decrease the intensity of attacks from heavy category to medium. The effectiveness of 3 (three)attracktant types of Hypotan 500 SL, Atrakop 500 L and Koptan L to trap the pest H. hampei Ferr on a coffee field with protective trees and without protective trees was relatively no different. Keywords : attracktant; attack intensity; coffee fruit grinder; protective tree